2013
DOI: 10.1111/cup.12198
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous meningioma: a potential diagnostic pitfall in p63 positive cutaneous neoplasms

Abstract: Cutaneous meningiomas are divided into three groups. Type I lesions present at birth and are derived from ectopic arachnoid cells. Type II lesions usually present in adults and are derived from arachnoid cells surrounding nerve bundles. Type III lesions are due to direct extension or metastasis from dural-based neoplasms. Dural-based meningiomas are known to express p63. The aim of our study is to examine the expression of p63 in type II and type III meningioma. Two cases of cutaneous meningioma (type II and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Fox et al [37] have reported negative Keratin 5/6 expression in two cases of ectopic cutaneous meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Fox et al [37] have reported negative Keratin 5/6 expression in two cases of ectopic cutaneous meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Both types I and II lesions are thought to represent hamartomas and carry significant histopathologic overlap 7 . Type III lesions arise from either direct extension or metastasis from an intracranial meningioma 8 …”
Section: Discussionmentioning
confidence: 99%
“…7 Type III lesions arise from either direct extension or metastasis from an intracranial meningioma. 8 F I G U R E 2 Coronal section of magnetic resonance imaging showing a type III cutaneous atypical meningioma of the scalp Histopathologically, type I lesions are typically located in the deep dermis and are composed of pseudovascular clefts, which may be lined by scattered eosinophilic epithelioid meningothelial cells with minimal to no atypia in a collagenous nodule. They may also present with a cystic channel or with well-circumscribed nodules.…”
Section: Case Studymentioning
confidence: 99%
“…Owing to the similar results from immunohistochemical staining of type II and III meningiomas, imaging involving a combination of x-ray and MRI or CT and MRI was performed to appropriately classify the tumors. 27,37,38,[40][41][42][43] Based on our findings, both x-rays and CTs were unable to show the presence of intracranial exchange, resulting in MRIs being the recommended imaging technique to determine whether a lesion is dural based. 37,38,41…”
Section: Discussionmentioning
confidence: 99%
“…The broad differential diagnosis when evaluating lesions of the head/scalp area can make it difficult to identify cutaneous meningiomas. 37,38 The clinical presentation of firm, subcutaneous nodules normally associated with cutaneous meningiomas is similar to that of a lipoma, trichilemmal cyst, basal cell carcinoma, squamous cell carcinoma, Merkel cell carcinoma, or metastasis of another tumor. 38,39 As a result, all the cases in Table 1 conducted a histological examination with the aid of immunohistochemistry because histopathological findings by themselves are nonspecific.…”
Section: Discussionmentioning
confidence: 99%